Pelatihan Pembuatan Pupuk NPK Complate Plus Dari Kotoran Hewan Ternak Sebagai Upaya Meningkatkan Ekonomi Di Desa Tirtanadi, Kecamatan Labuan Haji Kabupaten Lombok Timur - Dodi Febrian; Baiq Hadiyani; Titik Husnawati Amini; Muhamad Akrom; Muh. Ariadi Muslim; Susi Mariani (Elevasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2026)
Desa Tirtanadi is one of the villages in the Labuan Haji District, East Lombok Regency, which has a lot of potential, both in agriculture, plantations, and livestock. The reality is that the farmers of Tirtanadi Village complain about the limited government-subsidized fertilizers, forcing them to buy both subsidized and non-subsidized fertilizers at exorbitant prices. This results in high agricultural costs, reduced crop yields, and even losses for them, prompting the village government to produce its own agricultural fertilizer needs for the community to achieve village independence, reduce agricultural operational costs, improve soil fertility, and realize sustainable agriculture. One of the solutions that can be implemented is utilizing livestock manure as organic fertilizer to reduce the problem of livestock waste and assist farmers with the issue of subsidized fertilizer shortages. Therefore, socialization and training activities are very necessary regarding the training on making organic fertilizer based on livestock manure, as this can become a promising opportunity and hold economic value for the local community.